Identifying desired qualifications, tasks, and organizational characteristics of practice managers-a cross-sectional survey among group practice physicians in Germany - Clemens Schricker; Christoph Strumann; Jost Steinhäuser (BMC, 2022)
Abstract Background The increase of centralization developments in primary and secondary care practices may cause the organizational needs to increase as well, as the practices grow in size. This continuous change is observed in different stages in various countries since, from the perspective of a physician, it is reinforced by the benefits it adds to flexible work configuration, professional exchange and specialization. However, in order to benefit from the joint practice system, the proper managerial skills of practice managers are required, as doctors are not naturally prepared to fulfill such tasks. This study thus aims to gain insight into physicians' views in group practices and acquire a greater understanding of expectations towards practice management and the emerging role of practice managers (PM). Methods A cross-sectional study design was employed which utilized an anonymous online questionnaire. In total, 3,456 physicians were invited to participate in the study between February 8th and March 17th 2021 by the Association of Statutory Health Insurance Physicians of Baden-Württemberg, Germany. Bivariate and multivariate analyses were applied to characterize the expectations of physicians towards practice management. Results The survey yielded 329 replies (9,5%). 50% of the participating practices already had a PM employed. In general, these practices were larger than practices without a PM. Most physicians (85%) considered a medical background to be essential for the task of a PM. While practices without a PM considered it important for PMs to have medical qualifications, practices with a PM favored qualifications in business administration. 77.2% of physicians preferred to educate and recruit PMs out of their current practice staff. Competence in organizational tasks, such as coordination of tasks and quality management, was considered to be an essential skill of a PM and had the highest agreement levels among those surveyed, followed by staff management of non-physicians, billing, bookkeeping, staff management of physicians and recruiting. Based on multivariate regression analysis, larger practices valued the role of a PM more and were more likely to employ a PM. Notably, the effect that size had on these items was more substantial for generalists than specialists. Conclusions The benefits and importance of PMs as well as the potential for delegation are recognized, in particular, by larger practices. The positive feelings that physicians who already employ PMs have towards their contribution to ambulatory care are even more significant. Pre-existing medical support staff has been identified to be the most desirable candidates for taking on the role of PM.